Kualitas guru terhadap kompetensi pedagogik dan tenaga kependidikan Madrasah Ibtidaiyah - Fahma, Tsaniyah Faradila Fahma Fara (Maliki Interdisciplinary Journal, 2026)
This research aims to examine the essential role of Elementary Madrasah (MI) teachers as primary character builders and implementers of three main mandates: advancing basic competencies (literacy and numeracy), facilitating basic science learning, and instilling fundamental values. To effectively carry out these tasks, mastery of pedagogical competencies is mandatory, demonstrated through comprehensive research assessments and a commitment to continuous professional quality improvement. Improving the quality of Elementary Madrasah (MI) teachers cannot be achieved entirely; it must be supported by a solid ecosystem. In this context, the synergy of the Leading Teacher Program (PGP) plays a key role. The Leading Teacher Program (PGP) serves as a driver of competence and leadership, focusing on improving teachers’ pedagogical skills, as well as their management and leadership capabilities (Satriawan et al., 2021). This synergy includes close coordination between various relevant parties (central and regional governments, BBGP/BGP, school institutions, and Leading Teachers). From a systemic perspective, the Synergy of the Leading Teacher Program (PGP) provides empowerment to all Education Personnel. The Leading Teacher Program (PGP) strategically improves the quality of Functional Staff (Teachers) while simultaneously strengthening Structural Staff (Principals) with pedagogically-based leaders. This model successfully creates a supportive learning environment and encourages collaboration between educators, making it crucial in overcoming obstacles to meeting competency standards, especially in Madrasah Ibtidaiyah institutions. Thus, the Leading Teacher Program (PGP) ensures that the self-development efforts of Madrasah Ibtidaiyah Teachers are supported by integrated policies, which ultimately guarantee that learning transformation at the elementary education level is achieved sustainably and in line with national education goals.